Observation of strong wavelength-shifting in the argon-tetrafluoromethane system - Amedo, P.; González-Díaz, D.; Brunbauer, F. M.; Fernández-Posada, D. J.; Oliveri, E.; Ropelewski, L. (Frontiers in Detector Science and Technology, 2023)
We report the scintillation spectra of Ar/CF 4 mixtures in the range 210-800 nm, obtained under X-ray irradiation for various pressures (1-5 bar) and concentrations (0-100%). Special care was taken to eliminate effects related to space charge and charge recombination, so that results can be extrapolated following conventional wisdom to those expected for minimum ionizing particles under the typical electric fields employed in gaseous instrumentation. Our study sheds light into the microscopic pathways leading to scintillation in this family of mixtures and reinvigorates the prospects of use in next-generation scintillation-based chambers.